Paliperidone Inducing Concomitantly Syndrome of Inappropriate Antidiuretic Hormone, Neuroleptic Malignant Syndrome, and Rhabdomyolysis - Jaspinder Kaur; Dileep Kumar; Mostafa Alfishawy; Ricardo Lopez; Issac Sachmechi (Case Reports in Critical Care)
Paliperidone, an active metabolite of risperidone, is a new atypical antipsychotic agent. Syndrome of inappropriate antidiuretic hormone (SIADH), neuroleptic malignant syndrome (NMS), and rhabdomyolysis are the uncommon side effects of psychotropic drugs. We report a case of 35-year-old male with schizoaffective disorder who was admitted for acute-on-chronic exacerbation of his psychotic disorder for which intramuscular paliperidone 234 mg injection was given. Two days later, the patient developed hyponatremic seizures secondary to SIADH which was treated with hypertonic saline. On the third day, he developed high grade fever and severe muscle rigidity with raised creatine phosphokinase (CPK) and liver enzymes levels. He was treated with dantrolene 100 mg, bromocriptine 2.5 mg, and lorazepam 2 mg. Our patient required management of the three rare conditions following treatment with paliperidone. This case highlights the need for health care providers to be aware of the rare, potentially life threatening but preventable hyponatremia, NMS, and rhabdomyolysis as a possible adverse effect of paliperidone.